Generation z: the new driving force in tourism entrepreneurship - Dias, Á.; Pereira, L. (12th International Scientific Research and Innovation Congress., 2024)
Generation Z (Gen Z), individuals born between 1997 to 2012, is poised to revolutionize the tourism industry with their unique work-life balance expectations and entrepreneurial spirit. Unlike previous generations, Gen Z values flexibility, purpose, and personal growth above traditional career paths. As a result, they are seeking opportunities in the tourism sector that align with their values and provide opportunities for innovation and creativity. One of the defining characteristics of Gen Z is their strong emphasis on work-life balance. They are less likely to prioritize long hours and career advancement over personal well-being and lifestyle aspirations. This presents challenges for tourism businesses that traditionally rely on long hours and intense work schedules. However, it also presents opportunities to develop innovative business models and practices that align with Gen Z's values. This paper explores the intersection of Generation Z, tourism entrepreneurship, and innovation, examining how entrepreneurs can attract and retain this talented generation by fostering a work environment that promotes work-life balance, purpose, and personal growth. The paper delves into the unique characteristics of Gen Z entrepreneurs, highlighting their adaptability, technological savvy, and entrepreneurial drive. It also discusses how tourism entrepreneurs can leverage innovation to create experiences that resonate with Gen Z travelers, emphasizing experiential tourism, personalized travel, and sustainable tourism practices. By understanding the work-life balance expectations of Generation Z entrepreneurs and leveraging innovation to create meaningful experiences, tourism businesses can attract and retain this valuable segment of the workforce. By fostering a culture of flexibility, purpose, and growth, tourism entrepreneurs can tap into the entrepreneurial energy of Gen Z, leading to innovation and success in the ever-evolving tourism landscape.